(untitled) (Journal of Laboratory Animal Science, 2024)
A great number of preclinical and clinical studies have not only confirmed but have also extended the medicinal uses of species of the genus Phyllanthus mentioned in traditional medicine. We have examined some of the mechanisms underlying the analgesic effects of the extracts of Phyllanthus amarus and Phyllanthus fraternus against formalin induced nociception in mice. In addition, we also investigated the action of both the species against capsaicin-mediated pain. 20 μl of 2.5% formalin (0.92% formaldehyde), made up in phosphate-buffer solution, was injected intraplantarly in the right hindpaw. Animals were pre-treated with the extracts of Phyllanthus amarus and Phyllanthus fraternus and with specific receptor antagonists for evaluating the mechanisms of analgesic activity. 20 μl of capsaicin (1.6 μg/paw) was injected intraplantarly in the right hind paw. Animals were treated with the extracts of P. amarus and P. fraternus intraperitoneally (1-30 mg/kg) 30 min before, or orally (25-200 mg/kg) 60 min before capsaicin injection. Both the adrenergic receptor antagonists prazosin and yohimbine (0.15 mg/kg, i.p.) had no effect on the antinociceptive action caused by extracts of P. amarus (30 mg/kg, i.p.) and P. fraternus (30 mg/kg, i.p.). Treatment of animals with L-arginine (600 mg/kg) had no significant effect against the analgesic properties of P. amarus and P. fraternus. The extracts of Phyllanthus amarus and Phyllanthus fraternus given either intraperitoneally or orally caused marked and dose-related inhibition of capsaicin-induced pain. The current study suggest that their antinociceptive action is unrelated to central depressor action, interaction with α-adrenergic receptor or interaction with L-arginine nitric oxide pathway.